Luxury Consumption in India: Consumer Behavior, Market Trends, and Future Prospects - Gaur, Swapnil; Verma, Mohit (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
Luxury goods are defined as items that consumers acquire by spending a specific amount of money or an equivalent value, enhancing the consumer's social status or self-perception. These goods often elevate an individual’s standing socially, among peers, colleagues, or even in their own view. The luxury goods market has been growing steadily since the onset of capitalism, with people striving to set themselves apart through the purchase of exclusive products and services. Over time, such high-value, exclusive items earned the label "luxury," as they were primarily accessible to the wealthy, making luxury a symbol of affluence. In recent years, however, the desire for individuality and sophistication has extended luxury beyond the wealthy, reaching a broader, economically diverse audience. In emerging economies like India, this shift has driven significant growth in the luxury market. India’s luxury sector has fluctuated over the years, with increasing per capita income contributing to its expansion. Experts predict further substantial growth in the coming years, largely driven by the younger generation. This demographic’s perception of luxury goods differs markedly from that of previous generations, reflecting a changing view of what luxury signifies. Therefore, this study aims to explore the factors behind this generational shift in luxury consumption and how current luxury brands can adapt and benefit from these evolving perceptions. Indian luxury has grown from being a niche demand to a strong industry significantly driven by increasing affluence, globalization, and a younger demographic in the last two decades. This review takes a closer look at the development of luxury consumption in India, exploring the determinants of demand, motivations of consumers, and current market trends. From the conclusion, cultural values, social identity, and economic growth are the biggest contributors toward luxury consumption in India and hence need strategies to localize for this kind of marketplace. The article concludes with future directions that luxury brands may take within India but also the kind of difficulties they may experience.